2020
DOI: 10.1016/j.clnu.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Reference body mass index values and the prevalence of malnutrition according to the Global Leadership Initiative on Malnutrition criteria

Abstract: Background & aims: The Global Leadership Initiative on Malnutrition (GLIM) released new criteria for diagnosing and grading malnutrition. This study aimed to investigate the optimal reference values of body mass index (BMI) for discriminating severe malnutrition according to the GLIM criteria, as well as the prevalence of GLIM-defined malnutrition in the clinical setting. Methods: This study included 6783 patients aged 40 years, who were admitted to an academic hospital. Of the 1987 patients who presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 21 publications
4
96
1
Order By: Relevance
“…Results of the present study showed a 4-times higher prevalence of malnutrition when using GLIM instead of ESPEN criteria. This prevalence is similar to the 18% for adults older than 40 and 25.7% in the individuals older than 70 years reported in a cross-sectional study in community-dwelling Japanese older people, 31 which is, to authors' knowledge, the only study where GLIM criteria have been applied; therefore, further research would be needed to compare our findings. The authors consider that the close relationship found between malnutrition and mortality might be explained by the evidence-based close relationship between any of the five criteria that compose the new definition, which were selected due to their strong relationship with mortality, as described by Cederholm et al 32 The nature of the link between malnutrition and mortality is mediated by oxidative stress, altered micronutrient balance, catabolic changes, and inflammation (present in the definition as aetiologic criteria), and this damage in intracellular homeostasis leads to tissue dysfunction, organ failure, altered body composition, and weight loss (phenotypic criteria).…”
Section: Discussionsupporting
confidence: 86%
“…Results of the present study showed a 4-times higher prevalence of malnutrition when using GLIM instead of ESPEN criteria. This prevalence is similar to the 18% for adults older than 40 and 25.7% in the individuals older than 70 years reported in a cross-sectional study in community-dwelling Japanese older people, 31 which is, to authors' knowledge, the only study where GLIM criteria have been applied; therefore, further research would be needed to compare our findings. The authors consider that the close relationship found between malnutrition and mortality might be explained by the evidence-based close relationship between any of the five criteria that compose the new definition, which were selected due to their strong relationship with mortality, as described by Cederholm et al 32 The nature of the link between malnutrition and mortality is mediated by oxidative stress, altered micronutrient balance, catabolic changes, and inflammation (present in the definition as aetiologic criteria), and this damage in intracellular homeostasis leads to tissue dysfunction, organ failure, altered body composition, and weight loss (phenotypic criteria).…”
Section: Discussionsupporting
confidence: 86%
“…Although both these conditions are known to be associated with falls among older adults [41], this information was not recorded in the hospital's medical recording system, thereby preventing us from linking these conditions with the rest of the collected data. Third, BMI values that determine malnutrition may differ between Europeans and the Japanese [12]. Although many studies have reported ESPEN-defined malnutrition to be associated with malnutrition among Asian populations, a malnutrition diagnosis valid for the population under study would be better.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition may result in an extended hospital stay, increased frequency of re-admission, increased mortality [10], and failure to return home [11]. Malnutrition is present in approximately 25% of hospitalized older adult patients in acute care [12]. Aging individuals are susceptible to malnutrition [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we only used the ESPEN criteria in diagnosing malnutrition, although the latest diagnostic criteria from GLIM had been published. 2,26 Although many clinical studies in Japanese individuals have reported an association of ESPEN criterion malnutrition with clinical outcomes, no report has examined whether the cut-offs for BMI and lean body mass index, components of the ESPEN criterion malnutrition diagnosis, are optimal cut-offs for Japanese people. [27][28][29] GLIM-defined malnutrition requires the presence of phenotypic and etiologic criteria, whereas ESPEN-defined malnutrition does not involve etiologic factors.…”
Section: Discussionmentioning
confidence: 99%